UJI TOTAL FLAVONOID DARI EKSTRAK AIR AUN KELOR (Moringa oleifera) DAN SECANG (Caesalpinia sappan L.) - Dhigna Luthfiyani Citra Pradana; Aprilla Ayu Wulandari (Jurnal Insan Farmasi Indonesia, 2019)
Moringa trees in Indonesia are considered mystical, but Moringa has many benefits. Moringa oleifera leaves have active compound-containing phenol, flavonoids, and tannins which can act as antioxidants, prevent hyperglycemia and hyperlipidemia. Caesalpinia sappan L is also often consumed, known as wedang uwuh. Caesalpinia sappan L. contains brazilin which can reduce blood glucose. The antioxidant activity of water extracts on moringa and Caesalpinia sappan L leaves needs to be known before conducting in vivo tests, therefore the purpose of this study is to determine the total flavonoids of water extracts of Moringa and Secang leaves. In this study conducted experimentally with a completely randomized design. The total flavonoid test uses the UV visible spectrophotometric method at a wavelength of 435 nm. Total flavonoids in the water extract of Moringa leaves were 7.79 mg / g and Secang 3.7 mg / g.